Cognitive performance and associated factors among primary school children in artisanal and small-scale gold mining communities in northwestern Tanzania - Joel L. Maduhu; Elias C. Nyanza; Theresia Maduka; Neema Kayange (Public Health and Toxicology, 2024)
Introduction Cognitive performance deficit remains a major public health problem in developing countries. Emerging evidence from the literature suggests environmental exposure to chemical substances influences neurocognitive development in children. The study determined the prevalence of cognitive deficits and associated factors among primary school children aged 8–12 years in artisanal and small-scale gold mining (ASGM) communities where exposure to toxic chemical elements is common.